2008
DOI: 10.1158/0008-5472.can-07-2879
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Stimulates the Growth of Cyclin D1–Overexpressing Breast Cancer Cells by Promoting the Activation of Signal Transducer and Activator of Transcription 3

Abstract: De novo or acquired resistance to tamoxifen is a major clinical challenge for the management of estrogen receptor (ER)-positive breast cancers. Although cyclin D1 overexpression is associated with a better outcome for breast cancer patients, its overexpression is also linked to tamoxifen resistance. We previously reported that the beneficial effect of cyclin D1 correlates with its ability to repress the antiapoptotic transcription factor signal transducer and activator of transcription 3 (STAT3). In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 30 publications
4
47
0
Order By: Relevance
“…Inhibition of constitutive STAT3 activation in diverse tumor cell lines, by the blocking of tyrosine kinase signaling using small-molecule inhibitors, has been repeatedly associated with growth suppression and induction of cell death (Epling-Burnette et al, 2001;Garcia et al, 2001;Aggarwal et al, 2006). In addition, it has been reported that upregulation of STAT3 phosphorylation in breast cancer cells reduces the efficiency of chemotherapy (Aggarwal et al, 2006;Gariboldi et al, 2007;Ishii et al, 2008), whereas suppression of STAT3 activation increases the proapoptotic effect of doxorubicin (Gariboldi et al, 2007). Accordingly, we assumed here that inhibition of STAT3 activation by NDRG2 in breast cancer cells may promote apoptosis induced by a chemotherapeutic agent, such as doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of constitutive STAT3 activation in diverse tumor cell lines, by the blocking of tyrosine kinase signaling using small-molecule inhibitors, has been repeatedly associated with growth suppression and induction of cell death (Epling-Burnette et al, 2001;Garcia et al, 2001;Aggarwal et al, 2006). In addition, it has been reported that upregulation of STAT3 phosphorylation in breast cancer cells reduces the efficiency of chemotherapy (Aggarwal et al, 2006;Gariboldi et al, 2007;Ishii et al, 2008), whereas suppression of STAT3 activation increases the proapoptotic effect of doxorubicin (Gariboldi et al, 2007). Accordingly, we assumed here that inhibition of STAT3 activation by NDRG2 in breast cancer cells may promote apoptosis induced by a chemotherapeutic agent, such as doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, constitutive activation of STAT3 has frequently been observed in breast cancer and malignant breast cancer cell lines. In addition, STAT3 activation in breast cancer cells decreases the efficiency of chemotherapy (Aggarwal et al, 2006;Gariboldi et al, 2007;Ishii et al, 2008), while STAT3 inhibition increases the proapoptotic effect of doxorubicin (Gariboldi et al, 2007). Thus, the identification of upstream genes regulating STAT3 activation is critical for increasing tumor cell sensitivity to anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Low expression of cyclin D1 expression was, conversely, associated with high risk of cancer recurrence. Thus, overexpression of cyclin D1 was reported to be actually beneficial for breast cancer survival, associated with inverse tumor grade, smaller tumor size, and improved relapse-free and overall survival of breast cancer patients (Ishii et al, 2008). As a mechanism for such counterintuitive function, it has been proposed that cyclin D1 represses the activity of signal transducer and activator of transcription 3 (STAT3) (Ishii et al, 2006).…”
Section: Cell Cycle Regulation In Tamoxifen Resistant Breast Cancersmentioning
confidence: 99%
“…Estrogen is required for normal proliferation and differentiation of breast epithelial cells and is implicated in the development and progression of breast cancer [4]. The classical mechanism of estrogen action mainly involves two members of the nuclear receptor superfamily, the estrogen receptor (ER) α and ERß [5].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, partial antagonists of ERα, such as 4-hydroxytamoxifen (OHT), may display cell-and promoter-specific agonist effects that are thought to be due, at least in part, to AF1 activity and/or to the ability to recruit cofactors [10][11][12]. OHT was the first antiestrogen approved for the clinical management of ER-positive breast cancers and has been recommended as first-line treatment for the past three decades [4]. Despite the beneficial effects of OHT for patients at all stages of ER-positive breast cancer [13], the major obstacle to its use is the development of tamoxifen-resistance which either occurs de novo or in patients showing initial benefits [14].…”
Section: Introductionmentioning
confidence: 99%